Analisis Kepuasan Kerja Pegawai, Dampak dari Penerapan Servant Leadership, Motivasi Intrinsik, dan Lingkungan Kerja (Sudi pada Kantor Satuan Polisi Pamong Praja dan Wilayatul Hisbah Bireuen) - Chairullah Chairullah; Ibrahim Ibrahim (Aceh Cooperative Care, 2026)
This research article analyzes employee job satisfaction, the impact of servant leadership implementation, intrinsic motivation, and the work environment. The study involved 71 employees of the Civil Service Police Unit and Wilayatul Hisbah Office of Bireuen Regency. The quantitative associative method was used, and data analysis was conducted using path model statistics. The results found: (1) Servant leadership, intrinsic motivation, and the work environment are mutually causal and have both direct and indirect effects on job satisfaction. Servant leadership, intrinsic motivation, and the work environment each contribute 40.08% to job satisfaction, 46.89% to intrinsic motivation, and 36.8% to work environment. (2) Servant leadership, intrinsic motivation, and the work environment simultaneously contribute 62.7% to employee job satisfaction.